Unprecedented biodesalination rates–Shortcomings of electrical conductivity measurements in determining salt removal by algae and cyanobacteria. (15th January 2022) - Zafar, Abdul Mannan; Javed, Muhammad Asad; Aly Hassan, Ashraf
Abstract: Phormidium keutzingianum performed biodesalination of brackish water (10 g/L). The electrical conductivity (EC) was measured to evaluate the salt concentration over 80 days of cyanobacterial inoculation. Anion concentrations were measured using ion chromatography to estimate salt removal. EC-based measurements showed ∼8–10% removal efficiency in the first 20 days. However, the removal efficiency based on chloride ion concentration showed ∼40% removal in the same time frame. The pH increase was observed with growth of algal biomass. The increasing pH proposes the formation of hydroxyl and carbonate ions. Sulfuric acid was added at day 110 to neutralize them. At pH 4, the EC reduced significantly to about ∼37% confirming the chloride removal. EC should not be used to measure salt reduction as it is an obscure parameter, and therefore, EC is not the best choice to measure salinity removal using algae. Some recently published studies used only EC to estimate biodesalination, and it is anticipated that salt removal is misrepresented in those studies. Graphical abstract: Image 1 Highlights: Salt removal of more than 40% is possible via biodesalination within 20 days. Salinity based on electrical conductivity does not agree with chloride concentration. CO3 2− /HCO3 − ions contributed to the electrical conductivity estimation. Electrical conductivity underestimated ionic removal compared to anion analysis.